Acute Toxicity Evaluation of Mango (Mangifera indica L.) Leaf and Peel Extracts on Zebrafish (Danio rerio) Embryos - Lusi Agus Setiani; Zaldy Rusli; Dinda Sabina Oktavia (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Mangiferin is the main flavonoid compound found in Mangifera indica L. (mango), known for its antioxidant and anti-inflammatory activities. In addition to the leaves, secondary metabolites such as alkaloids, flavonoids, and triterpenoids are also present in mango peels, contributing to their antibacterial properties. This study aimed to evaluate the acute toxicity of mango leaf and peel extracts using the Zebrafish Embryo Acute Toxicity Test (ZFET). The test was conducted over a 96-hour post-fertilization (hpf) period using zebrafish (Danio rerio) embryos exposed to five different concentrations of the extracts: 50 ppm, 100 ppm, 150 ppm, 200 ppm, and 250 ppm, along with an internal control using embryo water. Observed parameters included mortality rate and morphological abnormalities such as pericardial edema, yolk sac edema, spinal deformities, and tail malformations. Probit regression analysis revealed LC?? values of 156.133 ppm for mango leaf extract and 160.353 ppm for mango peel extract at 96 hpf. According to the EPA toxicity classification, both extracts fall into the practically non-toxic category. These findings provide preliminary evidence that mango leaf and peel extracts are relatively safe and have potential for further development into natural product-based formulations. However, additional research is required to support their clinical applications and long-term toxicological profiles.